(untitled) (PANGEEA, 2025)
ABSTRACT: Crăciunelu de Jos (Alba County) – Local geographical denominations. Crăciunelu de Jos (Alba County) is one settlements whose existence can be traced several centuries ago. It is located in the central area of the Târnava Valley, at a distance of approximately 6 kilometers from the city of Blaj. The precincts of the village have evolved alongside the meadow as well as on the lower terraces of the valley, at an altitude of 235 m, and the rural area – with a surface of approximately 1.600 hectares- stretches alongside Lopadei Hills, in the North, and Secaşelor Highlands (the subdivision Cergăului Highlands), in the South. Due to the variety of the natural elements and the anthropic activities, in Crăciunelu de Jos one can notice 67 geographical denominations - 6 landforms, 8 streams, 3 forests/riverside coppices, 6 village areas and 44 lands - each of them benefitting from a brief characterization. Key words: geographical denominations, Crăciunelu de Jos, Alba County